Experience, childhood, and care of oneself: challenges to the current school knowledge and practices - Pagni, Pedro Angelo (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This paper deals with the problem of experience and its possible languages between school knowledge and practices. Its objective is to find the different possibilities of thinking the experience in the educational praxis, based on the contemporary philosophical categories of event and childhood as well as on the genres of poetic language and testimony. In order to do so, it is reconstructed a genealogy of the transformation of educational praxis into pedagogical art in its relationships with childhood whether as a government goal or as a subject, revealing the domination states that constitute them and pointing out their potential of resistance to the actual one. It is also stated that this event breaks into in the aesthetic dimension of experience and concurs in order to interrupt the order of discourse, making subjects of educational praxis think about it and causing care of oneself to become an ethic attitude put together with an aesthetics of experience. Thus, this research aims at restoring the dignity of experience among school knowledge and practices.